2006
DOI: 10.1007/s10143-006-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Giant cavernous hemangiomas: report of three cases

Abstract: Giant cavernous hemangiomas occur very rarely, and little has been reported about their behavior. In this case report three cavernous hemangiomas with a diametric measure between 6 cm and 7 cm and distinct features will be described. A 36-year-old female patient presented with headache and nausea. A CT scan disclosed a large circumscribed tumor with strong contrast enhancement in the temporo-parieto-occipital region of the right cerebral hemisphere and extension into the right cerebellar hemisphere. A 35-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…We defined GCMs as cavernoma with a diameter greater than 6 cm in accordance with Lawton et al 15) . With this definition, we found that only 14 cases have been repoted in the literature 7,14,23,24) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We defined GCMs as cavernoma with a diameter greater than 6 cm in accordance with Lawton et al 15) . With this definition, we found that only 14 cases have been repoted in the literature 7,14,23,24) .…”
Section: Discussionmentioning
confidence: 97%
“…GCMs are very rare and little has been reported about their clinical characteristics 7,14,23,24) . But, the definition of GCMs is arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…1 These vascular anomalies are composed of abnormal cavernous endothelial-lined spaces lacking smooth muscle and intervening neural tissue. Within these channels, static blood flow results in thrombosis, hematoma organization, and eventual calcification.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case reports describe a tumefactive appearance on MRI, as the lesions demonstrate an apparent infiltrative pattern and significant perilesional edema. 1,6,13,14 These masses may mimic the appearance of high-grade glial neoplasms or hemorrhagic tumors, such as, oligodendrogliomas and metastases. Further complicating the differential diagnosis are largely cystic masses without surrounding edema or an infiltrative appearance.…”
mentioning
confidence: 99%
“…GCM are very rare and usually not considered in the differential diagnosis of large tumour. Our literature search could locate only 16 cases of GCM (1, 4,5,7,8,12,13,15,20,23,37) including the two cases in the present report, fulfilling our definition of GCM (Table I).…”
Section: Casementioning
confidence: 99%